Does the Strategy of Risk Group Testing for Hepatitis C Hit the Target? - Jovanovic, Mirjana R.; Miljatovic, Aleksandar; Puskas, Laslo; Kapor, Slobodan; Puskas, Dijana L. (Frontiers in Pharmacology, 2017)
In the European Union, it is estimated that there are 5.5 million individuals with chronic infection of hepatitis C. Intravenous drug abuse is undoubtedly the key source of the hepatitis C epidemic in Europe and the most efficient mode of transmission of HCV infections (primarily due to short incubation time, but also because the virus is introduced directly into the blood stream with the infected needle). Potentially high-risk and vulnerable populations in Europe (and the world) include immigrants, prisoners, sex workers, men having sex with men, individuals infected with HIV, psychoactive substance users etc. Since there is a lack of direct evidence of clinical benefits of HCV testing, decisions related to testing are made based on indirect evidence. Clinical practice has shown that HCV antibody tests are mostly adequate for identification of HCV infection, but the problem is that this testing strategy does not hit the target. As a result of this health care system strategy, a large number of infected patients remain undetected or they are diagnosed late. There is only a vague link between screening and treatment outcomes since there is a lack of evidence on transmission risks, multiple causes, risk behavior, ways of reaching screening decisions, treatment efficiency, etc. According to results of limited number of studies it can be concluded that there is a need to develop targeted programmes for detection of HCV and other infections, but there also a need to decrease potential harms